Subtype Diagnosis of Sporadic Creutzfeldt–Jakob Disease with Diffusion Magnetic Resonance Imaging. Issue 3 (22nd December 2020) - Bizzi, Alberto; Pascuzzo, Riccardo; Blevins, Janis; Moscatelli, Marco E. M.; Grisoli, Marina; Lodi, Raffaele; Doniselli, Fabio M.; Castelli, Gianmarco; Cohen, Mark L.; Stamm, Aymeric; Schonberger, Lawrence B.; Appleby, Brian S.; et al.
Abstract : Objective: Sporadic Creutzfeldt–Jakob disease (sCJD) comprises several subtypes as defined by genetic and prion protein characteristics, which are associated with distinct clinical and pathological phenotypes. To date, no clinical test can reliably diagnose the subtype. We established two procedures for the antemortem diagnosis of sCJD subtype using diffusion magnetic resonance imaging (MRI). Methods: MRI of 1, 458 patients referred to the National Prion Disease Pathology Surveillance Center were collected through its consultation service. One neuroradiologist blind to the diagnosis scored 12 brain regions and generated a lesion profile for each MRI scan. We selected 487 patients with autopsy‐confirmed diagnosis of "pure" sCJD subtype and at least one positive diffusion MRI examination. We designed and tested two data‐driven procedures for subtype diagnosis: the first procedure—prion subtype classification algorithm with MRI (PriSCA_MRI)—uses only MRI examinations; the second—PriSCA_MRI + Gen—includes knowledge of the prion protein codon 129 genotype, a major determinant of sCJD subtypes. Both procedures were tested on the first MRI and the last MRI follow‐up. Results: PriSCA_MRI classified the 3 most prevalent subtypes with 82% accuracy. PriSCA_MRI + Gen raised the accuracy to 89% and identified all subtypes. Individually, the 2 most prevalent sCJD subtypes, MM1 and VV2, were diagnosed with sensitivities up to 95 and 97%, respectively. The performances of both procedures did not change in 168 patients with longitudinal MRI studies when the last examination was used. Interpretation: This study provides the first practical algorithms for antemortem diagnosis of sCJD subtypes. MRI diagnosis of subtype is likely to be attainable at early disease stages to prognosticate clinical course and design future therapeutic trials. ANN NEUROL 2021;89:560–572